Some aspects of the integrated control of cucurbits fruit fly Dacus ciliatus (Loew) (Diptera: Tephritidae) on cucumber crop - Safaa Zakaria Baker (Tikrit Journal of Pure Science, 2023)
Field experiment  was carried out during the autumn season in the Alam area in the east of Tikrit to study the integration of the three types of chemical pesticides (Media, Wide and Decis) and four cucumber varieties (Gazer, Amin, Najim and  Zena) and Mass trapping technique by using Macphil traps that they contained female food attractive FLYCAP MASS to control  cucurbits fruit fly Dacus ciliatus (Loew) in three open fields, the first field applied pesticides only, the second field applied pesticides and Mass trapping technique traps, and the third field for comparison (without pesticides and traps), was conducted two sprays for pesticides, the first spray after fruits setting directly and the second spray after week of the first spray .